The Formation Of A Humanistic Approach To The Development Of Student Individuality In Pedagogy At The Beginning Of The 20th Century - Shakhlo Mamaniyozovna Khudoykulova (Euro Asian Journal Publishing, 2023)
this article analyzes the factors of the formation of the educational process of freedom, increasing the position of educational entities, stimulating creative creativity, directing the learner to self-development and perfection, forming an individual educational trajectory, and democratizing and humanizing the educational process from a pedagogical point of view
Keywords: education; educationupbringing; humanistic